Pedestrian Environment Optimization of Xiaobailou District of Tianjin - Liu, Yanan; He, Jie (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 6, 2019)
Promoting pedestrian activities in cities is an important green transportation approach to mitigate negative modern urban problems such as traffic congestion, air pollution, as well as health issues like obesity. The efficiency of the pedestrian environment connected to an urban transit station is significant for green urban transportation approach. This paper focuses on the pedestrian environment around subway stations and investigates shortcomings on walkability of Xiaobailou District of Tianjin. The research team introduces theoretical findings on walking accessibility and preferences to support urban design applications in Xiaobailou District within the pedestrian accessible scope of the subway station. This paper illustrated spatial phenomena and optimizations from the pedestrian flow system, facilities, street boundary, road cross sections, and so on for improving pedestrian environment. These efforts will create better accessibility to the metro station and consequently improve peoples’ preference of taking subway for urban transportation.